Investigating teachers’ mathematics pedagogical content knowledge on ratio and proportion: Does it exist in teaching? - Rooselyna Ekawati; Fou-Lai Lin; Ahmad Wachidul Kohar (Jurnal Cakrawala Pendidikan, 2022)
There is a widespread agreement that Mathematics Pedagogical Content Knowledge (MPCK) become one of the key resources for teaching mathematics effectively. This qualitative research investigates the existence of primary teachers’ MPCK in mathematics teaching practice on ratio and proportion. Data were collected from the recorded videos of teaching observations of three primary teachers with different levels of Mathematics Content Knowledge (MCK) and MPCK selected from a paper and pencil test. A video observation instrument considering the MPCK factors’ framework for teaching ratio and proportion was used to explore the existence of MPCK in the teachers’ teaching practices. Data were analyzed by employing a whole-to-part approach of video-based data on three components of the teachers’ teaching practices on ratio and proportion, i.e., task level feature, the teaching of problem-solving strategies, and knowledge of students’ conceptual understanding. Results indicate that all the components of teachers’ MPCK can be observed in teaching practice appropriately or inappropriately due to teachers’ different levels of MPCK (Good, Medium, and Low). All MPCK factors were activated by the good teacher in her teaching appropriately differs from Medium and Low teachers. The Medium teacher needs more opportunities to learn about ratio and proportion task level features. The evidence leads to the opportunity to design a learning trajectory for In-service primary teachers that consider the integration of MPCK and MCK in balance.